AB0866 Advanced metrology in patiens with axial spondyloarthritis: lumbar or thoracic+lumbar measurements for spinal mobility assessment?. (12th June 2018) - Aranda-Valera, I.C.; Garcia-Luque, L.; Alcaraz-Clariana, S.; Garrido-Castro, J.L.; Martinez-Sanchez, I.; Gonzalez, C.; Gardiner, P.; Machado, P.M.; Collantes, E.; ,
Abstract : Background: Advanced technologies for measuring human mobility have recently emerged: motion capture, inertial measurement units (IMU) and wereable devices. Some of them are used for mobility assessment of rheumatic patients. 1 Certain devices analyse only lumbar mobility of the patients. Axial Spondyloarthritis (axSpA) reduces spinal mobility at all levels and not only at the lumbar level. Objectives: To analyse what is the contribution of the thoracic spine to spinal mobility, and if this contribution should be taken into account in the metrological assessment of patients with axSpA. Methods: 20 patients with axSpA and 20 age, BMI and sex-matched healthy subjects were recruited. An IMU sensor-based system (ViMove©) was used to measure spinal mobility. This system uses two IMU sensors and the angle between both is obtained in real time. Two tests were recorded: one with the recommended anatomical location (pelvis and L1) and another one aimed at combining lumbar +thoracic movement (pelvis and T3). Conventional metrology, radiographic structural damage (axSpA patients) and PROs were also collected. Results: The table shows the results obtained for measuring only lumbar or lumbar +thoracic mobility, in both groups. The contribution of the thoracic spine is expressed in% of the total movement. Pearson correlation coefficients (only for patients) with conventional metrology (BASMI), PRO questionnaires (BASDAI, BASFI and ASQoL) and structural damage (mSASSS) scores are also presented. Conclusions: Thoracic +Lumbar results reflect better the spinal mobility impairment of axSpA patients compared to lumbar spine assessments only. Compared to isolated lumbar spine assessment, the combined assessment showed better correlations with conventional metrology, disease activity, physical function, health-related quality of life and spinal structural damage. Despite this, the magnitude of the differences is not enough to reject the use of a system that only considers assessment of lumbar spinal mobility. Reference: [1] Garrido-Castro JL, et al. Assessment of spinal mobility in ankylosing spondylitis using a video-based motion capture system. Man Ther. 2012Oct;17(5):422–6. Acknowledgements: This study has been funded by Foreum (Foundation for Research in Rheumatology) Disclosure of Interest: None declared